Food recipe mobile application for allergist / Muhamad Harith Noor Affandee and Shahirah Mohamed Hatim - Noor Affandee, Muhamad Harith; Mohamed Hatim, Shahirah (Universiti Teknologi MARA, Perak, 2022)
People who develop allergy reactions often have limited access to certain foods. The technology of smart and mobile applications has emerged as important tools for people who have difficulties managing their food diet, especially those with serious illnesses and health risks. Providing a variety of options for these people in using a suitable mobile application for their diet management will be highly beneficial. This paper reports the research works on the food diet mobile application that can be customized according to some peoples’ needs and limitations. Based on the Waterfall model of System Development Life Cycle (SDLC), the mobile application has been developed for the Android platform by using the Android Studio software development tool. The application interfaces and usability testing results were presented in this paper to show the effectiveness of the food recipe mobile application. The usability results showed that the majority of users found that the mobile application was easy and convenient to be used. This paper presents the fundamental design and development methodology of a mobile application that can assist people with strict dietary and allergies problems to find suitable recipes.